2020
DOI: 10.3389/fendo.2020.00345
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Formation and Inactivation Following TBI: What we Know and Where we Could go

Abstract: Traumatic brain injury (TBI) is responsible for various neuronal and cognitive deficits as well as psychosocial dysfunction. Characterized by damage inducing neuroinflammation, this response can cause an acute secondary injury that leads to widespread neurodegeneration and loss of neurological function. Estrogens decrease injury induced neuroinflammation and increase cell survival and neuroprotection and thus are a potential target for use following TBI. While much is known about the role of estrogens as a neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 137 publications
2
15
0
Order By: Relevance
“…However, ERα is predominant in hypothalamic nuclei that control reproduction, sexual behavior, and appetite ( Osterlund and Hurd, 2001 ; Hedges et al, 2012 ; Barth et al, 2015 ), while ERβ is predominant in non-reproductive hypothalamic nuclei as well as in dorsal raphe nuclei, basal forebrain, prefrontal cortex, various temporal and parietal regions, posterior cingulate, and cerebellum ( Mitra et al, 2003 ; Sugiyama et al, 2010 ). While ERα and ERβ both contribute to the neuroprotective effects of estrogen, ERβ plays a larger role than ERα in supporting cognition by mediating neural plasticity, regulating brain-derived neurotrophic factor (BDNF), and promoting learning and memory ( Zhao et al, 2015 ), whereas ERα is the primary mediator of steroid induced neuroprotection, with known effects on neurovascular function and myelin repair ( Dubal et al, 2001 ; Duncan, 2020 ). GPER receptors are also widely distributed in brain, and most concentrated in hippocampus and amygdala ( Hadjimarkou and Vasudevan, 2018 ).…”
Section: Estrogen Function In Brainmentioning
confidence: 99%
“…However, ERα is predominant in hypothalamic nuclei that control reproduction, sexual behavior, and appetite ( Osterlund and Hurd, 2001 ; Hedges et al, 2012 ; Barth et al, 2015 ), while ERβ is predominant in non-reproductive hypothalamic nuclei as well as in dorsal raphe nuclei, basal forebrain, prefrontal cortex, various temporal and parietal regions, posterior cingulate, and cerebellum ( Mitra et al, 2003 ; Sugiyama et al, 2010 ). While ERα and ERβ both contribute to the neuroprotective effects of estrogen, ERβ plays a larger role than ERα in supporting cognition by mediating neural plasticity, regulating brain-derived neurotrophic factor (BDNF), and promoting learning and memory ( Zhao et al, 2015 ), whereas ERα is the primary mediator of steroid induced neuroprotection, with known effects on neurovascular function and myelin repair ( Dubal et al, 2001 ; Duncan, 2020 ). GPER receptors are also widely distributed in brain, and most concentrated in hippocampus and amygdala ( Hadjimarkou and Vasudevan, 2018 ).…”
Section: Estrogen Function In Brainmentioning
confidence: 99%
“…In recent years, several research groups demonstrated the effect of E2 as a possible therapeutic agent of TBI [19][20][21][22]. Accordingly, the aim of this review is to summarize the role and mechanism of action of E2 in TBI.…”
Section: Introductionmentioning
confidence: 99%
“…These include COMT, PIK3CA, RYR3, SRD5A2, STS, and SULT2A1, as well as variants of genes coding aromatase, androgen receptor (AR), estrogen receptors (ER) α & β, and 17α-hydroxylase (Fernández et al, 2015 , 2018 ; Smith et al, 2015 ; Yang et al, 2017 ; Fisher et al, 2018 ; Foreman et al, 2019 ; Theisen et al, 2019 ). In terms of sex differences in TBI, we have also identified differences in a number of these genes as well, including PIK3C, SULT2A1, aromatase, AR and ERs, and 17 hydroxylase (Garcia-Segura et al, 2003 ; Duncan and Saldanha, 2011 , 2013 ; Saldanha et al, 2013 ; Pedersen et al, 2018 ; Cook et al, 2020 ; Duncan, 2020 ). Suggesting that these genes may have variations in their response following TBI and can serve as first candidates for examining differences in gene expression.…”
Section: Sex Gender and Tbi: Beyond The Binarymentioning
confidence: 88%